AN ANALYSIS OF FACTORS AFFECTING SHU IN COOPERATIVES OF MICRO BUSINESS AND LABOR COOPERATIVE DEPARTMENT IN KEDIRI CITY - Supriyadi, Stevanus Gatot; Jatmika, Dodik (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to determine: (1) the effect of the members number on the remaining business results (SHU), (2) the effect of the loans amount on the remaining business results, (3) the effect of the working amount capital on the remaining business results (SHU), (4) Number of Members, Amount of Loans, and Amount of Working Capital, to Remaining Business Results (SHU) under the auspices of the 2016 micro business and labor cooperative office in Kediri. The research population consisted of 64 cooperatives in 2016 spread over 3 sub-districts in Kediri City. Data collection method with documentation. The data analysis techniques used include 1) Classic Assumption Test which includes Normality Test, Linearity Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, 2) Hypothesis Testing using simple regression method, multiple regression, The results showed that: (1) there is no significant partial effect of the variable number of members (X1) on the residual income (Y) of the cooperative in Kediri City, (2) there is no significant partial effect of the variable amount of member loans (X2) on remaining results of business (Y) at the cooperative in Kediri City. Keywords: Number of Members, Amount of Loans, Amount of Capital, and Remaining Business Results